Pregnant women knowledge about prenatal development: Support for health education - Fernandes, Carolina Barretos; Picon, Fernando Silva; Paviotti, Ana Beatriz; Canevari, Thalita da Silva [UNESP]; Pinheiro, Osni Lázaro; Spadella, Maria Angélica (Faculdade de Filosofia e Ciências, 2013)
Introduction: there is a series of studies related to intrauterine development, with significant advances in the elucidation of its molecular regulation and signalization, it is possible to notice that the perception by the pregnant woman about the development of the conceptus is not addressed in literature. The current studies on the pregnant woman perceptions about the conceptus are related to psychological aspects involving the fetus personification. A better understanding about the pregnant woman representations related to conceptus development can support the elaboration of educative actions, aiming at a qualified and humanized prenatal and puerperal care. Objective: to analyze the knowledge, worries and beliefs of a group of pregnant women regarding the prenatal development. Methods: a qualitative study was carried out, through semi structured individual interviews. The answers from the pregnant women were evaluated by the content analysis technique, under the thematic modality. Results: i t was observed that certain prenatal development processes are known by the pregnant women. This knowledge involves the following categories: physical characteristic and organic functions of the conceptus, the conceptus sex, establishment of the mother-conceptus bond, revelations of the ultrasound screening, concerns during the pregnancy and influence of superstitious beliefs in the pregnancy. Probably this knowledge has been transmitted by society, family, health team or through previous pregnancy experiences. However, this knowledge is misunderstood in its whole, presenting little correlation between the information accessed by the pregnant and, how much and how it was understood and assimilated. Conclusions: Therefore, interventions are needed, by means of health education.
Keywords: Embryonic and fetal development; Health education; Pregnancy; Qualitative research